Chondrogenic differentiation of mesenchymal stem cells through cartilage matrix-inspired surface coatings - Zhao, Mingyan; Gao, Xiang; Wei, Jinsong; Tu, Chenlin; Zheng, Hong; Jing, Kaipeng; Chu, Jiaqi; Ye, Wei; Groth, Thomas (Frontiers in Bioengineering and Biotechnology, 2022)
The stem cell niche comprises soluble molecules and extracellular matrix components which provide chemical and mechanical cues that determine the differentiation of stem cells. Here, the effect of polyelectrolyte multilayer (PEM) composition and terminal layer fabricated with layer-by-layer technique (LBL) pairing either hyaluronan [in its native (nHA) and oxidized form (oHA)] or chondroitin sulfate (CS) with type I collagen (Col I) is investigated on chondrogenic differentiation of human umbilical mesenchymal stem cells (hUC-MSCs). Physical studies performed to investigate the establishment and structure of the surface coatings show that PEM composed of HA and Col I show a dominance of nHA or oHA with considerably lesser organization of Col I fibrils. In contrast, distinguished fibrilized Col I is found in nCS-containing PEM. Generally, Col I-terminated PEM promote the adhesion, migration, and growth of hUC-MSCs more than GAG-terminated surfaces due to the presence of fibrillar Col I but show a lower degree of differentiation towards the chondrogenic lineage. Notably, the Col I/nHA PEM not only supports adhesion and growth of hUC-MSCs but also significantly promotes cartilage-associated gene and protein expression as found by histochemical and molecular biology studies, which is not seen on the Col I/oHA PEM. This is related to ligation of HA to the cell receptor CD44 followed by activation of ERK/Sox9 and noncanonical TGF-β signaling-p38 pathways that depends on the molecular weight of HA as found by immune histochemical and western blotting. Hence, surface coatings on scaffolds and other implants by PEM composed of nHA and Col I may be useful for programming MSC towards cartilage regeneration.